Systematic review of diplommatinid land snails (Caenogastropoda, Diplommatinidae) endemic to the Palau Islands. (2) Taxonomic revision of Hungerfordia species with low axial ribs - Yamazaki, Kazunori; Yamazaki, Midori; Ueshima, Rei (Zootaxa, 2015)
Hungerfordia Beddome, 1889 is a terrestrial caenogastropod genus of the family Diplommatinidae endemic to the Palau (Belau) islands. Hungerfordia is radiated within the Palau islands and exhibits substantial morphological diversity. In this paper, the taxonomy of Hungerfordia species with low axial ribs is revised. Hungerfordia polymorpha (Crosse, 1866), H. inflatula (Crosse, 1866), H. crassilabris crassilabris (Beddome, 1889), H. lutea lutea (Beddome, 1889), H. ringens ringens (Crosse, 1866), H. pyramis pyramis (Crosse, 1866), and H. aurea (Beddome, 1889) are redescribed based on the syntypes and newly collected materials. The following new taxa are described: H. aspera sp. nov., H. basodonta sp. nov., H. microbasodonta sp. nov., H. rudicostata sp. nov., H. unisulcata sp. nov., H. longissima sp. nov., H. eurystoma sp. nov., H. crenata sp. nov., H. crassilabris tridentata subsp. nov., H. crassilabris attenuata subsp. nov., H. lutea hemilaevis subsp. nov., H. loxodonta sp. nov., H. omphaloptyx sp. nov., H. robiginosa sp. nov., H. angaurensis sp. nov., H. ringens rotundata subsp. nov., H. ringens ventrinodus subsp. nov., H. pyramis pteroma subsp. nov., H. spinoscapula sp. nov.